THE INFLUENCE OF INCENTIVES, MOTIVATION AND WORK ABILITY ON JOB PERFORMANCE OF BHAKTI HUSADA HEALTH VOCATIONAL SCHOOL TEACHERS - Hendra Rustama; Mahfud; Weti Kurniawati (PT. Berkah Digital Teknologi, 2023)
Purpose of the study — This study aims to find out: How much influence does Incentives, Motivation and Work Ability simultaneously have on the work performance of Teachers of Bhakti Husada Kuningan Health Vocational School both partially and simultaneouslyResearch method— This research design uses a quantitative approach. Quantitative approach, survey method. This type of research is a causal associative research with data analysis techniques using Multiple Linear Regression analysis. Place of research at Bhakti Husada Kuningan Health Vocational School, the population of Bhakti Husada Kuningan Health Vocational School teachers totaling 34 people, the total sample.Result— The results of this study indicate: 1) Incentives partially have a positive and significant effect on the work performance of Teachers of SMK Kesehatan Bhakti Husada Kuningan by 52.1%, the remaining 47.9% are influenced by other factors. 2) Motivation partially has a positive and significant effect on the work performance of Teachers of SMK Kesehatan Bhakti Husada Kuningan by 39.4% while the remaining 60.6% is influenced by other factors. 3) Work ability partially has a positive and significant effect on the work performance of Teachers of SMK Kesehatan Bhakti Husada Kuningan by 15.6% while the remaining 84.4% is influenced by other factors. 4) There is a positive and significant influence. Incentives, motivation and work ability simultaneously have a positive and significant effect on the work performance of the Teachers of SMK Kesehatan Bhakti Husada Kuningan by 90.6%, the remaining 9.4% is influenced by other factors.Conclusion— The study found that Incentives, motivation and work ability all have a positive and significant effect on the work performance of teachers at Bhakti Husada Kuningan Health Vocational School. The combined influence of these factors is 90.6%. Practical Implications: The study suggests that providing incentives, increasing motivation, and improving work ability can lead to improved work performance for teachers at Bhakti Husada Kuningan Health Vocational School. Social Implications: The study highlights the importance of providing incentives, motivation, and work ability to teachers in order to improve their work performance. This can lead to better education outcomes for students and improved healthcare services in the long run.